The fluorescence from the chromophore of the purple membrane protein. - Govindjee, R (1978)
The fluorescence from the purple membrane protein (PM) of Halobacterium halobium and its relation to the primary photochemical events have been studied. The emission spectrum at 77 degrees K has structure, with peaks at 680, 710-715, and 730-735 nm. The excitation spectrum shows a single peak centered at 580 nm. This and a comparison of the fluorescence intensity at 77 degrees K under a variety of conditions with the amounts of the bathoproduct (or K, the only photoproduct seen at this temperature) formed suggest that the source of the fluorescence is the purple membrane itself, not the photoproduct. From the difference in several of their properties, we suggest that the fluorescing state of the pigment is different from the excited state which leads to photoconversion.